Cost-effectiveness of warfarin medication Therapy adherence clinic (WMTAC) versus usual Medical clinic (UMC) at Kuala Lumpur Hospital. - Shafie, Asrul Akmal (Universiti Sains Malaysia, 2014)

(untitled)
Systematic anticoagulation management clinic is now recommended to manage warfarinized atrial fibrillation (AF) patients. In Malaysia, the service is recently introduced as pharmacist managed Warfarin Medication Therapy Adherence Clinic (WMT A C). The objective of the present study was to assess the cost effectiveness of anticoagulation clinic in comparison with usual medical in Kuala Lumpur Hospital (KLH). KLH is 2302 bedded government tertiary referral hospital in Malaysia.